2000
DOI: 10.1109/36.843023
|View full text |Cite
|
Sign up to set email alerts
|

Effective permittivity of mixtures: numerical validation by the FDTD method

Abstract: The present paper reports the results of an extensive numerical analysis of electromagnetic fields in random dielectric materials. The effective permittivity of a two-dimensional (2-D) dielectric mixture is calculated by FDTD simulations of such a sample in a TEM waveguide. Various theoretical bounds are tested in light of the numerical simulations. The results show how the effective permittivity of a mixture with random inclusion positionings is distributed. All possible permittivity values lie between Wiener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
153
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(173 citation statements)
references
References 17 publications
10
153
0
Order By: Relevance
“…The quasistatic limit has also been used to argue that EM scattering will not be significant in heterogeneous media at long wavelengths, and thus the EM field will be insensitive to microstructural variations at the size scale of the inclusions. 36,37 However, the aggregation results in this study showed that small changes in microstructure affected macroscopic properties in the quasistatic limit, although the macroscopic composition (average particle volume fraction) remained constant. Additionally, the simulation results were by and large insensitive to the scale of the heterogeneities with respect to the incident field wavelength.…”
Section: Applicability Of the Quasistatic Limitmentioning
confidence: 52%
See 1 more Smart Citation
“…The quasistatic limit has also been used to argue that EM scattering will not be significant in heterogeneous media at long wavelengths, and thus the EM field will be insensitive to microstructural variations at the size scale of the inclusions. 36,37 However, the aggregation results in this study showed that small changes in microstructure affected macroscopic properties in the quasistatic limit, although the macroscopic composition (average particle volume fraction) remained constant. Additionally, the simulation results were by and large insensitive to the scale of the heterogeneities with respect to the incident field wavelength.…”
Section: Applicability Of the Quasistatic Limitmentioning
confidence: 52%
“…16 FE calculations have also been combined with the method of boundaryintegral equations (BIE) to simulate single inclusions of various shapes, including ellipsoids and cylinders, in 2D and 3D unit cells. 14 Similarly, the FDTD method has been used to model 2D mixtures containing up to 265 inclusions (1.0 inclusion volume fraction), 36,37 and to model the EM properties of biological tissues using periodic stacks of 30-100 spherical cells; 21 Other 6 approaches used to model the permittivity of random media include the transmission line matrix (TLM) method, which was applied to 2D simulations of 64-127 inclusions in a square periodic unit cell (0.5-1.0 inclusion volume fraction), 38 and the lattice Boltzmann method, which used 2D simulations to model fluid aggregation (wetting) in multiphase microporous materials. 39 Multipole expansion methods are efficient tools for modeling field interactions in arbitrary 3D configurations of spherical particles since the fields for a particle can be defined by a relatively small number of expansion coefficients rather than a large number of grid values as required for approaches such as the FE method.…”
Section: Introductionmentioning
confidence: 99%
“…(17) is the lower bound for the predication of effective permittivity, 14 numerical results is slightly higher than analytical solutions.…”
mentioning
confidence: 86%
“…The idea is to start from the Maxwell-Garnett equation (I) and to treat arbitrary volume fractions f by selfconsistently embedding the matrix and inclusion phases in an effective medium. It is also known as the Polder-van Santen formula, self-consistent field theory (SCF) or simply effective medium theory [16,17]. In solid state physics, the Bruggeman theory is closely related to the coherent-potential approximation (CPA) for binary alloys [IS, 19,20].…”
Section: Scientific Background: Bruggeman Modelmentioning
confidence: 99%